Single Walled Carbon Nanotube/Trititanate Nanotube Composite Fibres - C. Dechakiatkrai (2018)
A new combination of using biocompatible molecules as dispersants for both inorganic and organic single-walled carbon nanotubes (SWNT), followed by fiber spinning into a coagulation bath, was reported. Chitosan-titanate and titanate-SWNT dispersions were prepared from an acidic solution of Chitosan, which were ultrasonicated using pulse for 60 min and a high power sonic tip. Samples of the fibers, or of films from the dispersions were placed into wells of 96-well polystyrene cell culture plates and soaked overnight in two changes of culture media. Optical micrographs of the dispersion used in the spinning of fiber results in the alteration of spinning conditions and is responsible for the formation of a rough surface in the initial stages of gel fiber formation. No redox activity is observed from the fibers and all fibers displayed swelling when cycled while maintaining their structural integrity.